La agricultura familiar campesina y comercialización directa :caminos hacia el buen vivir en el cantón Cotacachi - Lanchimba Guandinango, María Elena (2016)
The present article seeks to make a contribution to the analysis and discussion of the importance of family farming and direct marketing in the construction of buen vivir or sumak kawsay in Cotacachi. This subject comes from a need to demonstrate concrete actions and progress made in each of the localities studied, in order to add body to the theoretical construction of el buen vivir, and in this way demonstrate its effectiveness and the need for increased State support of these practices, which are oftentimes rendered invisible. Based on this premise, we have done an extensive review of texts, documents and official information, which has provided the basis for the understanding, analysis, argumentation and structure of this article. The essay is organized into four parts. The first is an analysis of development and its results, from which we demonstrate the need to build new alternatives like el buen vivir. The second part seeks to define and differentiate family farming from capitalist industrial agriculture, covering the principal theories that define peasant farming. The third part aims to show the current panorama of family farming in Ecuador and highlight its contributions to the construction of sumak kawsay in the region. Finally, the article ends with the conclusions that allow us to corroborate the multiple virtues and contributions of family farming in order to achieve better living conditions for different sectors of the population.